Measuring urban walkability index for Petaling Jaya / Ishak Che Abdullah, Mohammad Yusup and Zulkifli Ahmad Zaki - Che Abdullah, Ishak; Yusup, Mohammad; Ahmad Zaki, Zulkifli (College of Built Environment, 2023)
Green neighbourhood is one of the initiatives taken by PLANMalaysia to reduce the nation's overall greenhouse gas emissions.